Genital HIV-1 Shedding With Dolutegravir (DTG) Plus Lamivudine (3TC) Dual Therapy. (15th December 2018) - Gianella, Sara; Marconi, Vincent C.; Berzins, Baiba; Benson, Constance A.; Sax, Paul; Fichtenbaum, Carl J.; Wilkin, Timothy; Vargas, Millie; Deng, Qianqian; Oliveira, Michelli F.; Moser, Carlee; Taiwo, Babafemi O.
Abstract : Supplemental Digital Content is Available in the Text.